Display Device of Information to Car Driver - KOVÁĈIK, PETER (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
The article deals with possibilities of information imaging to car driver. It mentions to development and exploitation of electronics to display complex and well-arranged information that is necessary at intensive traffic. The topic is completed by amount of graphical material that is needed for demonstrative visualization to reader in compliance with principles of attractiveness and visual demonstration used at dual education as progressive method at present time.